Flow and Transport in Coastal Aquifer‐Aquitard Systems: Experimental and Numerical Analysis - Jiaxu Zhang; Chunhui Lu; Chengji Shen; Yuxuan Liu; Adrian D. Werner; Chenming Zhang (Water Resources Research)
Abstract Coastal aquifers are commonly layered, and thus, a clear understanding of groundwater flow and salt transport in layered coastal aquifers is important for managing fresh groundwater. However, the influence of leakage between adjacent aquifers on flow and transport processes remains largely unknown where the influence of tides is considered. This study used laboratory experiments and numerical simulation to examine the processes of flow and transport within a tidal aquifer‐aquitard system (i.e., an unconfined aquifer underlain by a semi‐confined aquifer, with an intervening thin aquitard). The laboratory‐scale observations of the current study are the first observations of offshore fresh groundwater within a semi‐confined coastal aquifer. The numerical and laboratory results are in close agreement, revealing that upward leakage from the semi‐confined aquifer into the saltwater wedge of the overlying unconfined aquifer caused buoyant instabilities to form. The development of freshwater fingers created complex saltwater‐freshwater mixing, leading to mixed saltwater influx‐efflux patterns across the sloping aquifer‐ocean interface. Compared with non‐tidal conditions, tidal forces reduced the net upward leakage from the semi‐confined aquifer to the overlying unconfined aquifer. This increased the horizontal flow toward the sea, which in turn reduced the extent of the saltwater wedge in the semi‐confined aquifer. The higher rates of both fresh and saline submarine groundwater discharge (SGD), caused by tides, led to lower groundwater ages in the semi‐confined aquifer. These findings have important implications for unveiling the complex characteristics of seawater intrusion, SGD and geochemical hotspots within layered coastal aquifers.